(untitled) - Morris, Deborah Gray (London, 2002)
Textbook offers a step-by-step approach including ratio and proportion, formula, and dimensional analysis. Features a focus on key content, more than 200 drug labels, critical thinking, and more. CD-ROM contains additional problems
Keywords: Pharmaceutical arithmetic,Nursing,Điều dưỡng,Dược số học; Mathematics